ACUTE APPENDIX- STATISTICS ON PATIENTS IN SOUTHEAST REGION OF THE REPUBLIC OF NORTHERN MACEDONIA IN THE PERIOD FROM 2015 TO 2020 - Zhu, Jihe; Arsovska, Blagica; Kozovska, Kristina (International Journal of Research -GRANTHAALAYAH, 2021)
In this research the analyzed data were obtained from the Department of Social Medicine of the Center for Public Health at PHI General Hospital - Strumica for patients with acute appendicitis from Strumica and from the department for Statistics of the Center for Public Health at PHI General Hospital - Gevgelija for patients with acute appendicitis from Gevgelija. 361 people diagnosed with acute appendicitis were analyzed in the period from 2015 to 2020. According to the results most of the patients were hospitalized in 2015 (20.2%) and 2016 (20.2%). The majority of respondents are aged 0-24 years (67.5%), while males have a higher risk of developing this disease (55, 9%). in 2017 the number was 40 (14.9%), in 2018, 43 (16%), and in 2019 the number of hospitalized with acute appendicitis was 40 (14.9%), equal to that in 2017. The average age at hospitalization is 23.4 years, 22.8 years for men and 24 years for women. In the number of hospitalized people belonging to the first three age groups from 0 - 24 years, 25-44 years and 45-54 years (0-54), there is a higher prevalence of male (57.4%) compared to female patients (42.6%), while the number of hospitalized patients belonging to the age groups of 55-64, 65-74 and over 74 years there is a higher representation of female (58.3%) compared to male patients (41.7%). The average morbidity rate per 10,000 inhabitants in the Southeast region is 4.1, with an average rate of 3.5 in Gevgelija and an average rate of 4.8 in Strumica per 10,000 citizens. The incidence of acute appendicitis is highest in children, adolescents and young adults, and continuously decreases with age.